Animated Life Writing - Petryna, Brandon (Imaginations)

(untitled) (York University, 2023)
This paper proposes that the medium of animation enriches the narrative portrayal of lived experiences. Despite the rise in popularity of animation as a tool for storytelling on digital video sharing platforms, as of yet, little scholarship explores the impacts of animation on life writing narratives. In an encounter with animation production, I develop an original example of these animated narratives which I term animated life writing. Through the approaches of critical making and research in practice, by which I have created an accompanying animated video, the benefits and drawbacks of animation are explored with a particular focus on embodiment in life writing and the liveliness that is generated by cartoons.